INOVASI DALAM MANAJEMEN PENDIDIKAN: TINJAUAN LITERATUR DAN REKOMENDASI UNTUK PRAKTIK - Endang Yuda Nuryenda; Loso Judijanto; Muhammad Sukron Fauzi; Rossa Ramadhona; Yudi Hendrilia (LPPM Universitas Ekasakti, 2024)
This research aims to identify and analyze various innovations in education management, evaluate their impact on the quality of education and student learning outcomes, and develop practical recommendations that can be implemented by education stakeholders in Indonesia. Thus, it is hoped that this research can contribute to creating a learning environment that is more inclusive, relevant and responsive to community needs, as well as overcoming the challenges faced in the education system. This research uses a type of library research or literature study, where researchers rely on various literature sources to collect relevant data and information. With a qualitative approach, this research focuses on analyzing data in the form of words or descriptions, allowing researchers to explore the context and meaning behind the information found. The results of this research show that innovation in educational management involves curriculum development, use of technology, improvement of human resources, stakeholder participation, and evaluation systems. Competency-based curriculum and project learning increase educational relevance and student engagement, while the integration of information and communications technology (ICT) increases the efficiency of data management and communications. Ongoing training for teachers is important for the quality of teaching, and parent and community involvement increases accountability. Practical recommendations include adaptive curriculum development, technology training, community engagement programs, and data-driven evaluation to create inclusive and effective educational environments.